2012
DOI: 10.1180/claymin.2012.047.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite in Argentinian deposits: origin and textural constraints

Abstract: AB ST R ACT : In Argentina, the only halloysite deposits found so far are located in the southwest of the province of Rio Negro. The areas are named Mamil Choique and Buitrera, separated by 50 km in a W-E direction. The deposits are located in pyroclastic rocks, rhyolitic tuffs and ignimbrites.The aim of this paper is to determine the origin of the alteration, any relationship between the processes in Mamil Choique and Buitrera, and the factors which controlled the halloysite formation. The work was based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…The latter paper also concluded that there is an increase in the substitution of Al by Fe as the spheroidal halloysite transforms into tubular and platy forms. Cravero et al (2012) concluded that in Mamil Choique and Buitrera deposits, halloysite is formed from the dissolution of volcanic glass and that the particle morphology depends on the original texture of the rock; spheroidal halloysite is related to rocks with low porosity, and tubular particles are related to rocks with open spaces similar to what was found by Adamo et al (2001). Halloysite coming from different deposits has low iron content, and there are no differences associated with different morphologies.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The latter paper also concluded that there is an increase in the substitution of Al by Fe as the spheroidal halloysite transforms into tubular and platy forms. Cravero et al (2012) concluded that in Mamil Choique and Buitrera deposits, halloysite is formed from the dissolution of volcanic glass and that the particle morphology depends on the original texture of the rock; spheroidal halloysite is related to rocks with low porosity, and tubular particles are related to rocks with open spaces similar to what was found by Adamo et al (2001). Halloysite coming from different deposits has low iron content, and there are no differences associated with different morphologies.…”
Section: Resultsmentioning
confidence: 82%
“…Cravero et al (2012) indicated that probably waters circulating towards small basins filled with these rocks (thus giving the current pocket shape of the deposits) came into contact with them for long periods of time, and halloysite formed after the dissolution of glass. In Urquiza, where kaolinite predominates, the parent rock is acid plutonic (granite, granodiorite).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations